Utvärdering av berikning för baktrisk kamel(Camelus bactrianus) på Furuviksparken - Backman, Evelina (SLU/Dept. of Animal Environment and Health (until 231231), 2017)
The wild Bactrian camel (Camelus bactrianus) is a critically endangered species. The Bactrian camel can be found in some of the more remote places on earth, three places in northern China and one place in southern Mongolia. There are about 600 individuals left in China and about 300 individuals left in Mongolia. Despite the Bactrian camel being an umbrella species, there is very little research to be found about them. The camel’s morphology and behaviour makes it uniquely adapted for life in the deserts. Motivation is a process within the brain which controls what behaviour and physiological changes that are expressed and when the animal expresses them. It is important to investigate motivation to be able to understand animal welfare and the origin of abnormal behaviours. Behavioural needs is a term used to describe animals needs to express a certain specific behaviour pattern no matter what environment it is or if the physiological need is fulfilled. If the behavioural need is not fulfilled it can lead to stress, frustration and stereotypic behaviour. Environmental enrichment is a wide concept and the definition varies among different authors. An author defines it as an improvement of biological functions of the animal in captivity by modifications in its environment. There are many reasons for the use of environmental enrichment, it enhances the animal’s health and immune system, reduces stress, increases the number of behaviours performed by the animal and to make animals use their enclosures better. The aim of this study was to evaluate each enrichment and see if the camels used them, if all individuals use them and how the enrichment effects the behaviour of the camels. A pilotstudy was conducted the weekend before observation on the enrichments started, to get an idea of what kind of behaviour that should be a part of the ethogram. Control observations were made, with no access to any of the enrichments, before the evaluation of the enrichments started. This was conducted to get a baseline of performed behaviour by the camels. Three types of enrichment were evaluated for Bactrian camels during two weeks. One enrichment was activation balls, another was a scent on straw placed in different places in their enclosure, and the third enrichment was a log in which you could place food. The conclusions of this study was that some changes in behaviour could be seen, they all used the enrichment though individual differences could be observed. The activity level did not vary much between the control study and the studies with enrichment. More research is needed about the Bactrian camel and their behavioural need and welfare in captivity.